Adaptación y validación de la escala de pensamiento mágico de moral (EPM23) en adultos estudiantes y de nivel de educación superior de Lima Metropolitana - Cabredo Castillo, Benjamin Pedro (2021)
Magical thinking (MT) accounts for a way of reasoning divorced from the scientific laws of causality and of transmission of information that are culturally accepted, and that is related to various psychopathological conditions. There is an absence of psychometric instruments developed for the assessment of this variable in Lima, Perú. The present study aimed to adapt Moral’s Magical Thinking Scale (2012) in a sample of students and adults with postsecondary education from Lima’s metropolitan area. The sample size was 293: 115 persons with incomplete postsecondary studies, 142 with a degree in postsecondary studies and 36 with completed graduate studies. Evidence related to content validity were found through the item’s assessment in the domains of clarity and representativeness, which was executed by 8 expert judges and resulted in the modification of 5 items and the elimination of 1. Some items were modified according to the cultural background of the sample. A single factor internal structure, that explains 49% of the common variance and includes 22 items of the scale, was established; itshowed adequate loadings and communalities. Internal consistency results were satisfactory (¿ = .92, a = .89). MT scores differed between males and females with statistical significance (p = .002) and, therefore, different interpretation norms for this version of the scale were created for both groups. It is recommended, in future studies, to analyze divergent and criteria validity, to carry out confirmatory factor analysis, to implement a probability sampling method, and to include socioeconomic level as a variable.